2022
DOI: 10.1108/et-05-2021-0161
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual model of students' reflective practice for the development of employability competences, supported by an online learning platform

Abstract: PurposeIn a fast evolving labour market, higher education graduates need to develop employability competences. Key in becoming employable is the ability to reflect on learning experiences, both within a curriculum as well as extra-curricular and work placements. This paper wants to conceptualise how an online learning platform might entail a reflective practice that systematically supports students in reflecting on their learning experiences.Design/methodology/approachWhen studying online learning platforms fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 73 publications
(159 reference statements)
0
19
0
2
Order By: Relevance
“…Along with the development of computer technologies, big data, cloud computing, mobile Internet, and multimedia technologies, merely three presences within the CoI framework cannot satisfy the demands of learners. Online learning communities can provide a sea of learning resources and create interactive means of communication between teachers, peers, and online learning platforms (Heymann et al, 2022). This has greatly changed the learning environments, where many kinds of presences such as learning presence, telepresence, video-presence, and artificial intelligence presence may be needed (Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Along with the development of computer technologies, big data, cloud computing, mobile Internet, and multimedia technologies, merely three presences within the CoI framework cannot satisfy the demands of learners. Online learning communities can provide a sea of learning resources and create interactive means of communication between teachers, peers, and online learning platforms (Heymann et al, 2022). This has greatly changed the learning environments, where many kinds of presences such as learning presence, telepresence, video-presence, and artificial intelligence presence may be needed (Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The increasingly uncertain labour market prospects, technological progress, accelerating knowledge economy, high performance workplaces and forever changing industry specific demands necessitate that focused attention be paid to the employability of individuals over the course of their careers and accompanying job transitions (Heymann et al, 2022;Tymon, 2013). Moreover, escalating competition entails that employers make hiring decisions based on limited information about the candidate.…”
Section: Literature Review For Hypotheses Developmentmentioning
confidence: 99%
“…Withoutprofessional needs, employability does not exist. Capital (Shiyuan et al, 2022;Sulistiobudi, 2023;Arranz et al, 2022;Kulbo et al, 2022), career planning (Wu Yusheng, 2011;Denise Jackson et al, 2020;Minten et al, 2022;Finch et al, 2022), and digital skills (Mahajan, 2022;Heymann, 2022) have always been important factors that affect the employability of sports or other majors students, which have been the focus of previous research. However, multiple studies have shown that factors affecting employability involve only some aspects or process variables (Song Qiming, 2017), and the cultivation of students' employability lacks a systematic construction (Guo Xin, 2017).…”
Section: Abstract Cooperative Educationself-efficacyemployability Rel...mentioning
confidence: 99%